Oral delivery of pancreatitis‐associated protein by Lactococcus lactis displays protective effects in dinitro‐benzenesulfonic‐acid‐induced colitis model and is able to modulate the composition of the microbiota. (10th September 2019) - Breyner, Natalia M.; Vilas Boas, Priscilla Bagano; Fernandes, Gabriel; de Carvalho, Rodrigo D.; Rochat, Tatiana; Michel, Marie‐Laure; Chain, Florian; Sokol, Harry; de Azevedo, Marcela; Myioshi, Anderson; Azevedo, Vasco A.; Langella, Philippe; et al.
Summary: Antimicrobial peptides secreted by intestinal immune and epithelial cells are important effectors of innate immunity. They play an essential role in the maintenance of intestinal homeostasis by limiting microbial epithelium interactions and preventing unnecessary microbe‐driven inflammation. Pancreatitis‐associated protein (PAP) belongs to Regenerating islet‐derived III proteins family and is a C‐type (Ca +2 dependent) lectin. PAP protein plays a protective effect presenting anti‐inflammatory properties able to reduce the severity of colitis, preserving gut barrier and epithelial inflammation. Here, we sought to determine whether PAP delivered at intestinal lumen by recombinant Lactococcus lactis strain (LL‐PAP) before and after chemically induced colitis is able to reduce the severity in two models of colitis. After construction and characterization of our recombinant strains, we tested their effects in dinitro‐benzenesulfonic‐acid (DNBS) and Dextran sulfate sodium (DSS) colitis model. After the DNBS challenge, mice treated with LL‐PAP presented less severe colitis compared with PBS and LL‐empty‐treated mice groups. After the DSS challenge, no protective effects of LL‐PAP could be detected. We determined that after 5 days administration, LL‐PAP increase butyrate producer's bacteria, especially Eubacterium plexicaudatum . Based on our findings, we hypothesize that a treatment with LL‐PAP shifts the microbiota preventing the severity of colon inflammation in DNBS colitis model. These protective roles of LL‐PAP in DNBS colitis model might be through intestinal microbiota modulation.